2009
DOI: 10.1093/humrep/den380
|View full text |Cite
|
Sign up to set email alerts
|

A randomized double blind comparison of real and placebo acupuncture in IVF treatment

Abstract: Placebo acupuncture was associated with a significantly higher overall pregnancy rate when compared with real acupuncture. Placebo acupuncture may not be inert. Trial registered with HKClinicalTrials.com: number HKCTR-236.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
186
2
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(195 citation statements)
references
References 41 publications
(34 reference statements)
3
186
2
4
Order By: Relevance
“…32 Further, clinical trials that used sham acupuncture controls have suggested that sham acupuncture may be as effective as real acupuncture. [33][34][35] Since in our study we used non-penetrating needles at the acupuncture points as sham acupuncture, there is a possibility that the sham acupuncture may have provided sufficient stimulation to evoke a physiological effect. This suggestion is corroborated by an interesting finding of this study, in which patients' arthralgia symptoms showed a tendency to become worse when acupuncture treatment ceased in the sham and real acupuncture groups.…”
Section: Discussionmentioning
confidence: 99%
“…32 Further, clinical trials that used sham acupuncture controls have suggested that sham acupuncture may be as effective as real acupuncture. [33][34][35] Since in our study we used non-penetrating needles at the acupuncture points as sham acupuncture, there is a possibility that the sham acupuncture may have provided sufficient stimulation to evoke a physiological effect. This suggestion is corroborated by an interesting finding of this study, in which patients' arthralgia symptoms showed a tendency to become worse when acupuncture treatment ceased in the sham and real acupuncture groups.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the placebo group showed higher pregnancy rate. So et al (2009) obtained endometrial and subendometrial vascularity, serum cortisol concentration and the anxiety level were documented following both real and placebo acupuncture. There are several hypotheses to explain acupuncture action, but the exact underlying biological mechanism cause placebo effect (Amanzio & Benedetti, 1999;; Birch, 2006) but, even considering this possibility, the present among the groups.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence supporting the role of acupuncture in male subfertility is also insufficient, because most of the studies are uncontrolled case reports or case series in which the sample sizes were small. Due to that lack in the methodology, more double blinded studies with bigger sample sizes are necessary to confirm real influence of acupuncture in IVF (Stener-Victorin et al, 1999;; So et al, 2009). Even if the effects of acupuncture on the outcome of IVF -ve or tool for pain relief (Humaidan & Stener-Victorin, 2004) during transvaginal ultrasound-guided oocyte retrieval in patients who cannot tolerate the conventional conscious sedation because of its associated adverse effects.…”
Section: Discussionmentioning
confidence: 99%
“…Randomized trial studies have demonstrated that acupuncture is beneicial to reducing symptoms of depression [22], postraumatic stress disorders [23], postpartum stresses [24] as well as other psychosocial-emotional problems. However, the placebo of acupuncture required further researches as indicated by a randomized study that showed that placebo acupuncture signiicantly predicted higher overall pregnancy rate through reducing stress and anxiety levels in comparison with real acupuncture [25].…”
Section: C) Acupuncturementioning
confidence: 99%